GRAPHS OF EXACT SOLUTIONS OF ORDINARY DIFFERENTIAL EQUATIONS IN MAPLE (Web of Teachers: Inderscience Research, 2025)
This article analyzes the structure and structure of ordinary differential equations in the Maple system in a clear and sufficient manner. Compared to other systems, the solution and graph are clear and understandable.